Uji Beberapa Formulasi Pupuk Hayati Berbasis Limbah Tanaman pada Pembibitan Utama Kelapa Sawit (Elaeis Guineensis Jacq.) - Puspita, Fifi; Sampurno, Sampurno; Yulia, Urfa (Jurnal Agro Teknologi Tropika, 2016)
One of affected factor in oil palm seeds quality in main nursery was fertilization. One of organic fertilizer can be used was a biofertilizer. Theresearch aims to determine the effect and to obtain the best formulation of biofertilizer based on plant waste oil palm (Elaeis guineensis Jacq.) seeds growth in main nursery. The research was conducted from March to June 2014. This research used to Completely Randomized Design (CRD), consists of 5 treatments with 4 replication, then obtained 20 experimental units. Treatment given was: without biofertilizer formulation; Bacillus sp. + Pseudomonas fluorescens + liquid waste rice + 1 % chitin + 10 % molasses; Bacillus sp. + Pseudomonas fluorescens + tofu liquid waste+ 1 % chitin + 10 % molasses;Bacillus sp. + Pseudomonas fluorescens + sago liquid waste + 1 % chitin + 10 % molasses; Bacillus sp. + Pseudomonas fluorescens + PKS liquid waste + 1 % chitin + 10 % molasses. Parameters measured were increase of seed high, increase of midrib number, increase stump diameter, root volume, root crown ratio and dry seeds weight. Data were analyzed using ANOVA followed by DNMRT further test at 5% level. The results of the research showed, the several formulationof biofertilizers basedon plant waste effected on all observed parameters, but not effected on increase of midrib number. Biofertilizer formulations based on tofuliquid waste and PKS liquidwaste showed better results on all observed parameters.